La defensa de la cristiandad; las armadas en el Mediterráneo en la Edad Moderna - Bunes Ibarra, Miguel Ángel de (Cuadernos de Historia Moderna, 2006)
This account of the evolution of the Monarchy’s Mediterranean navies focuses on two main factors: firstly the development of their most characteristic ship, the galera (galley) and secondly the confrontation with the various Islamic powers settled on the Mediterranean’s shores. The two main reasons for the navy’s rapid growth from Charles V onwards were indeed the war against the Ottoman Empire and the need to set up regular communication channels between the different states governed by the Hapsburgs. The main factors that impinged on its development during these centuries, however, were its high cost, and the need of keeping squadrons permanently active to wage an ongoing war of attrition. By the eighteenth century changes in navigation and shipbuilding systems and in sea warfare had led to the extinction of a specific Spanish navy in the Mediterranean.
Keywords: Navies; Mediterranean; Ottoman Empire; Barbary Regencies